Modern economic and legal aspects in PR activities - Riabovolyk, Tetiana; Kramar, Bohdan (Herald of Economics, 2025)
Introduction. Modern PR activities play a key role in shaping public opinion, managing reputation, and facilitating communication between businesses, government institutions, and society. With the development of digital technologies and the increasing regulation of the information space, there is a growing need to comply with legal norms in the field of public relations. Failure to adhere to legal requirements can lead to reputational risks, administrative penalties, and even criminal liability. This article focuses on analyzing modern economic and legal aspects of PR activities, particularly examining legislative norms regulating public relations, data protection, copyright, liability for information dissemination, and ethical standards in the communication sphere. Special attention is given to challenges related to digital technologies, social media, and combating fake news.Objective. To explore modern economic and legal aspects of PR activities, including legislative regulations, copyright issues, data protection, countering fake information, and liability for violations of legal norms in the communication sphere.Research Methods. To achieve the stated objective, methods of analysis and synthesis, comparison, generalization and systematization, as well as logical and dialectical methods, were used.Results. Key legal challenges faced by PR professionals in modern conditions have been identified, including ethical norms, data protection, responsibility for disseminating false information, and advertising regulation on social media. A comparative analysis of key international and national legal acts regulating PR activities has also been conducted. The study examines major violations in PR activities and the corresponding liability.Discussion. Future research may focus on developing recommendations for PR professionals regarding legal compliance and analyzing legal changes related to the development of digital technologies and artificial intelligence in communications.